Mekanisme Pembentukan Alat Kelengkapan DPRD Kota Surabaya Periode 2009-2014 - Razali, Ubed Bagus (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: This article discusses about the Islamic political jurisprudence perspective against the formation mechanisms of formulating DPRD (City Council) of Surabaya for 2009-2014 through 3 stages. The first is the inauguration of the members and leaders of DPRD of Surabaya for 2009-2014. The second is the formation of fractions. The formulation of fractions is led by the fraction leader of 2009-2014 which consists of 1 chair and 1 vice chairman derived from the two parties who get the most first and second seat. The third is the adoption of the draft regulation rules (rules of procedure) and the establishment of the tools of DPRD of Surabaya for 2009-2014 which consists of a definitive chairman (1 chairman and 3 vice chairmen), a council, a commission, a Regional Legislation Board, a budget committee, as well as a honorary board. Within the Islamic political jurisprudence perspective, the formation mechanism of establishing tools of DPRD of Surabaya for 2009-2014 reflects the so called amar maâruf nahi munkar because the direct mechanism for setting based on the sequence number of the political partiesâ seats can prevent money politics and internal conflicts among the fellow legislators in Surabaya.Keywords: Formation, parliament, Islamic political jurisprudence.